Can heat and resource availability affect the pest status of African crickets? - (:unkn) unknown (My University, 2021)
Source Agritrop Cirad (https://agritrop.cirad.fr/605829/) * Autres projets (id;sigle;titre): ;AUTOMAR project;(FRA) Transfer and adaptatation of agro-ecological practices aimed at boosting the autonomy of market gardeners and crop safety in sub-Saharan Africa//
Keywords: African Research